KOMUNIKASI VERBAL DAN NON VERBAL PUSTAKAWAN DAN PEMUSTAKA DALAM PERSPEKTIF KOMUNIKASI ISLAM - Muhammad Bisri Mustafa; Siti Wuryan; Feni Meilani (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2021)
In libraries, the role of communication is very much needed in everyday life, where a library user and librarian can often interact and later can connect good communication in a library. Library users do not only ask for books, but library users will ask for information, therefore librarians are expected to be able to think creatively, inspire, and be able to motivate their librarians. The method used is the Journal of Analysis which has been published scientifically through e-books, e-journals, and scholarships which are then analyzed into short and descriptive journals. From the analysis, I got that communication in the library is very important because it can connect communication between library users and librarians who can give positive responses to each other.